Galectin signature in normal pregnancy and preeclampsia - Blois, Sandra M. (2013)
Members of the galectin family are expressed within the female reproductive tract and have been shown to be involved in multiple biological functions that support the progression of pregnancy. Specific expression patterns of different members of this family have been identified at the maternal decidua and on the placental side. In some cases, mechanisms by which galectins exert their functions have been delineated in adverse pregnancy outcomes. This review summarizes studies on galectins that have been documented to be important for pregnancy maintenance, either supporting the maternal adaptation to pregnancy or the placentation process. In addition, we focus our discussion on the role of galectins in preeclampsia, a specific life-threatening pregnancy disorder.